Anglikanizm po Newmanie. Diagnoza współczesnych teologów anglikańskich - Kopiec, Piotr (Studia Europaea Gnesnensia, 2016)
The artide presents symptoms of the crisis in Anglicanism using statistical data and theological approaches. Referring to the discussion within the Anglican church itself, author argues that liberal theology is one of the major factors which determine the condition of contemporary Anglican theology.